Recognition and Integration of The Madrasa Pedagogy of The Minority Muslim Nation Nepal: Case Study of Kapilvastu And Banke District - Saemah Shamim; Muhammad Nasir (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2023)
As a contemporary Islamic educational institution, the Madrasa (Islamic boarding school) has transformed into a public school with an Islamic identity. After years of being ignored, the Madrasas of a Muslim minority nation in Nepal, was finally been recognized by Nepal’s government in 2016. This article tends to dig out how the parents, Madrasah organizers, and students are perceiving this kind of inclusive formal education in the Madrasah system of Education. This research is Qualitative. Through the processes of reduction, exhibition, and verification, the information gathered from the observation, interview, and documentation was then examined. The triangulation of the data was then done as well. It produced several discoveries. Research results show that the action has increased Muslims' access to education, it is difficult to guarantee quality education because, according to the Research Centre for Educational Innovation and Development (CERID) 2018 report, the Madrasas lacked the physical infrastructure, teachers qualified to teach subjects in the mainstream, and other elements necessary for high-quality education. Following the government's effort to register madrasas as primary schools, it is now urgently necessary to analyze the effects, new trends, and problems. Conclusion, In order to foster the kids' religious behavior, tolerance, empathy, spiritual and non-spiritual understanding, and literacy skill, this study offers solutions for how to integrate the Madrasa curriculum program with the help of the government and the Ministry of Education.